MAN IN THE EPOCH OF THE HISTORICAL CATASTROPHE (THE NOVEL ‘FIELD’ BY L. ZUROV) (Proceedings of Southern Federal University. Philology, 2013)
Panesh B.N.Keywords: the emigration literature, Zurov, historical catastrophe, Russia, native land, the field, life and death.This article is devoted to the study of the literary world of L. Zurov, a Russian writer ofthe first emigration wave. The study is based on his novel ‘Polie’ (‘Field’), where the theme of a person involved in the thick of historical events is especially important. The Revolution and the Civil War change his view on life, the former basis is destroyed. But the man feels a strong link with the native land and believes in the Divine Providence. Ultimately, that gives him the power to resist chaos and death.